Change in The Status of A Certain Time Work Agreement to An Indefinite Time Work Agreement after Government Regulation in Lieu of Law Number 2 of 2022 Concerning Job Creation Takes Effect - Manalu, Evanto Pandora; Hoesin, Siti Hajati (Devotion : Journal of Research and Community Service, 2023)
The enactment of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation removes the derivative regulatory provisions of Law Number 11 of 2020 concerning Job Creation related to the Employment cluster. The change in status of a Fixed Time Work Agreement (PKWT) to an Unspecified Time Work Agreement (PKWTT) is regulated by Law Number 13 of 2003 concerning Manpower which generally regulates violations of work agreements in writing and in Indonesian language as a minimum and extension of work agreements, the period of the work agreement can change the status of PKWT to PKWTT. The aims are; (1) analyze and explain the implementation of PKWT to become PKWTT before the Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation and Law Number 11 of 2020 concerning Job Creation come into effect, and (2) analyze and explain the change in PKWT status to PKWTT after the Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation came into effect. This legal research is Normative/ Doctrinal Research. The results show provisions for changing PKWT to PKWTT are important because it relates to how workers have clarity in carrying out the daily work given by employers. Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation does not yet have derivative regulations and vacate the provisions of Government Regulation Number 35 of 2021 concerning Work Agreements for Specific Periods, Outsourcing, Working Time and Rest Time, and Termination of Employment.